2018
DOI: 10.1515/hsz-2017-0339
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-related peptidase 7 overexpression in melanoma cells modulates cell adhesion leading to a malignant phenotype

Abstract: We recently reported that human melanoma cells, but not benign melanocytes, aberrantly express kallikrein-related peptidase 7 (KLK7). Here, we show a KLK7 overexpression-mediated decrease of cell adhesion to extracellular matrix binding proteins, associated with downregulation of α5/β1/αv/β3 integrin expression. We also report an up-regulation of MCAM/CD146 and an increase in spheroid formation of these cells. Our results demonstrate that aberrant KLK7 expression leads to a switch to a more malignant phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…These cells showed a higher capacity for invasion than control cells, with, in parallel, a decrease in adhesion to fibronectin and vitronectin and a decrease in expression of α5β1 and αvβ3 integrins 54,55 . Moreover, these integrins were down regulated in melanoma cells modulating cell adhesion 56 . Together these data demonstrate that KLK5 could have opposite effects depending on cancerous or non‐cancerous cell characteristics.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These cells showed a higher capacity for invasion than control cells, with, in parallel, a decrease in adhesion to fibronectin and vitronectin and a decrease in expression of α5β1 and αvβ3 integrins 54,55 . Moreover, these integrins were down regulated in melanoma cells modulating cell adhesion 56 . Together these data demonstrate that KLK5 could have opposite effects depending on cancerous or non‐cancerous cell characteristics.…”
Section: Discussionmentioning
confidence: 80%
“…54,55 Moreover, these integrins were down regulated in melanoma cells modulating cell adhesion. 56 Together these data demonstrate that KLK5 could have opposite effects depending on cancerous or non-cancerous cell characteristics.…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that hKLKs have specific roles in the epithelial-mesenchymal transition. In fact, hKLK7 overexpression induces the production of CD146 (cluster of differentiation 146) ( 79 ), also known as melanoma cell adhesion molecule (MCAM), a surface glycoprotein that functions as a receptor for laminin subunit alpha 4, a matrix protein expressed in vascular walls, which could be related to melanoma metastasis ( 80 ). KLK6 −/− mice induced with carcinogenesis developed fewer tumors compared to wild-type animals, suggesting that KLK6 has a role in skin tumor development and progression ( 81 ).…”
Section: Skin Diseases and Their Relationship With Hklksmentioning
confidence: 99%
“…We found that kallikreinrelated peptidase 7 (KLK7) and keratin 7 (KRT7) were the most related genes in melanoma and renal cancer separately (Supplementary Figure 2). Aberrant expression of KLK7 has found to be related to melanoma aggressiveness by stimulating cell migration and adhesion (Delaunay et al, 2017;Haddada et al, 2018). KRT7 could distinguish the precursor lesions of papillary renal cell tumors, mucinous tubular and spindle cell carcinomas (Szponar and Kovacs, 2012).…”
Section: Gene Expression Analysis Of Cystatin E/m In the Merged Microarray-acquired Datasetsmentioning
confidence: 99%